Protein kinase C activity in boar sperm - Teijeiro, Juan Manuel (2017)
Male germ cells undergo different processes within the female reproductive tract to successfully fertilize the oocyte. These processes are triggered by different extracellular stimuli leading to activation of protein phosphorylation. Protein kinase C (PKC) is a key regulatory enzyme in signal transduction mechanisms involved in many cellular processes. Studies in boar sperm demonstrated a role for PKC in the intracellular signaling involved in motility and cellular volume regulation. Experiments using phorbol 12-myristate 13-acetate (PMA) showed increases in the Serine/Threonine phosphorylation of substrates downstream of PKC in boar sperm. In order to gain knowledge about those cellular processes regulated by PKC, we evaluate the effects of PMA on boar sperm motility, lipid organization of plasma membrane, integrity of acrosome membrane and sperm agglutination. Also, we investigate the crosstalk between PKA and PKC intracellular pathways in spermatozoa from this species. The results presented here reveal a participation of PKC in sperm motility regulation and membrane fluidity changes, which is probably associated to acrosome reaction and to agglutination. Also, we show the existence of a hierarchy in the kinases pathway. Previous works on boar sperm suggest a pathway in which PKA is positioned upstream to PKC and this new results support such model.